Projected estimates of cancer in Canada in 2020 - Brenner, Darren R.; Weir, Hannah K.; Demers, Alain A.; Ellison, Larry F.; Louzado, Cheryl; Shaw, Amanda; Turner, Donna; Woods, Ryan R.; Smith, Leah M. (Canadian Medical Association journal (CMAJ), 2020)
Cancer projections to the current year help in policy development, planning of programs and allocation of resources. We sought to provide an overview of the expected incidence and mortality of cancer in Canada in 2020 in follow-up to the Canadian Cancer Statistics 2019 report. We obtained incidence data from the National Cancer Incidence Reporting System (1984–1991) and Canadian Cancer Registry (1992–2015). Mortality data (1984–2015) were obtained from the Canadian Vital Statistics — Death Database. All databases are maintained by Statistics Canada. Cancer incidence and mortality counts and age-standardized rates were projected to 2020 for 23 cancer types by sex and geographic region (provinces and territories) for all ages combined. An estimated 225 800 new cancer cases and 83 300 cancer deaths are expected in Canada in 2020. The most commonly diagnosed cancers are expected to be lung overall (29 800), breast in females (27 400) and prostate in males (23 300). Lung cancer is also expected to be the leading cause of cancer death, accounting for 25.5% of all cancer deaths, followed by colorectal (11.6%), pancreatic (6.4%) and breast (6.1%) cancers. Incidence and mortality rates will be generally higher in the eastern provinces than in the western provinces. The number of cancer cases and deaths remains high in Canada and, owing to the growing and aging population, is expected to continue to increase. Although progress has been made in reducing deaths for most major cancers (breast, prostate and lung), there has been limited progress for pancreatic cancer, which is expected to be the third leading cause of cancer death in Canada in 2020. Additional efforts to improve uptake of existing programs, as well as to advance research, prevention, screening and treatment, are needed to address the cancer burden in Canada.